Determination of fire Resistivity of Door and Window Materials at Portharcourt Markets in Nigeria - Odaudu Ugbede Sunday (International Journal of Architectural Design and Planning, 2023)
The persistence of fire outbreaks in markets is a problem in Nigeria and the repetition of this problem is very frequent at Port Harcourt in Rivers State. To curtail this problem, research was made on the three major markets in Port Harcourt with the aim of determining the fire resistivity of their door and window materials, in order to generate guidelines for designing doors and windows of market buildings in Nigeria. The research made use of desktop study as the instrument for data collection. Then, the data were analyzed and checked by using content analysis technique, so as to validate the results. Among the findings are uses of ordinary windowpanes and their aluminium frames in the design of market buildings are not good practices against fires. Among the recommended guidelines are the design of all the window panes of market buildings must be metal type; the design of all the window frames of market buildings must be steel type, in order to ensure good practices against fires in Nigerian markets. Alternatively, the design of all the window panels of market buildings must be made up of any other fire-resistant material with a minimum of two hours resistance, in order to also ensure good practices against fires in Nigerian markets.
Keywords: Designing; doors and windows; fire; markets; windowpanes